Controlling the Pore Sizes and Related Properties of Inverse Opal Scaffolds for Tissue Engineering Applications. Issue 6 (31st January 2013) - Zhang, Yu Shrike; Regan, Kevin P.; Xia, Younan
Abstract Inverse opal scaffolds are finding widespread use in tissue engineering and regenerative medicine. Herein, the way in which the pore sizes and related physical properties of poly(D, L‐lactide‐co‐glycolide) inverse opal scaffolds are affected by the fabrication conditions is systematically investigated. It is found that the window size of an inverse opal scaffold is mainly determined by the annealing temperature rather than the duration of time, and the surface pore size is largely determined by the concentration of the infiltration solution. Although scaffolds with larger pore or window sizes facilitate faster migration of cells, they show slightly lower compressive moduli than scaffolds with smaller pore or window sizes.